Replication and characterization of CADM2 and MSRA genes on human behavior. Issue 7 (July 2017) - ,; Agee, Michelle; Alipanahi, Babak; Auton, Adam; Bell, Robert K.; Bryc, Katarzyna; Elson, Sarah L.; Fontanillas, Pierre; Furlotte, Nicholas A.; Hinds, David A.; Hromatka, Bethann S.; Huber, Karen E.; et al.
Abstract: Progress identifying the genetic determinants of personality has historically been slow, with candidate gene studies and small-scale genome-wide association studies yielding few reproducible results. In the UK Biobank study, genetic variants in CADM2 and MSRA were recently shown to influence risk taking behavior and irritability respectively, representing some of the first genomic loci to be associated with aspects of personality. We extend this observation by performing a personality "phenome-scan" across 16 traits in up to 140, 487 participants from 23andMe for these two genes. Genome-wide heritability estimates for these traits ranged from 5–19%, with both CADM2 and MSRA demonstrating significant effects on multiple personality types. These associations covered all aspects of the big five personality domains, including specific facet traits such as compliance, altruism, anxiety and activity/energy. This study both confirms and extends the original observations, highlighting the role of genetics in aspects of mental health and behavior.